ADOLESCENT IDIOPATHIC SCOLIOSIS: GENERAL REVIEW - Radwan Nouby Mahmoud, Yasser Mahmuod El-Banna, Ashraf A. Abdellatif ,Eslam Elsayed Elkhatib (Chelonian Research Foundation, 2025)
Adolescent Idiopathic Scoliosis (AIS) is an abnormal curvature of the spine exceeding 10 degrees, diagnosed in adolescence and in which the etiology is unknown. The gold standard for describing scoliosis is the Cobb angle. Smaller thoracic and thoracolumbar curves can be managed conservatively with observation or bracing, but corrective surgery may be indicated for rapidly growing or larger curves. Patients can be managed very well with a combination of conservative and surgical options. Outcomes for these children are excellent with sustained longer-term results.